Peningkatan Numerasi Awal Anak Usia Dini melalui Media Gambar Berbasis Lintasan Belajar Enaktif–Ikonik–Simbolik - Rostika, Sri; Rohmiati, Rohmiati; Idhayani, Nurul; Sitti Fatimah, Waode; Baen, Faldin (Diniyah: Jurnal Pendidikan Dasar, 2025)
Early numeracy is a critical foundation for young children’s readiness to learn mathematics. This study aimed to enhance early numeracy through picture media implemented gradually using an enactive–iconic–symbolic learning trajectory. A two-cycle classroom action research design was conducted in a preschool group at PAUD Ummushabri Kendari, involving 15 children. Data were collected through observations of instructional implementation and children’s development, performance and product assessments (matching quantities to number symbols, ordering numbers, and tracing number forms), and documentation. Data were analyzed descriptively using quantitative and qualitative procedures. Results showed steady improvements from the pre-intervention phase to Cycle I and further gains in Cycle II, reaching full class mastery. The strongest progress appeared in one-to-one correspondence and number ordering, while number symbol recognition improved after strengthening quantity–symbol mapping activities. Instructional implementation also improved, especially in consistent gradual support and managing transitions from pictorial representations to number symbols. These findings indicate that picture media is effective when positioned as a representational tool that connects counting experiences, visual representations, and number symbols through repeated, meaningful practice. Keywords: early numeracy; picture media; enactive iconic symbolic; number symbols; one-to-one correspondence; number ordering